Risk Factors for Recurrent Staphylococcus aureus Bacteremia. (21st June 2020) - Choi, Seong-Ho; Dagher, Michael; Ruffin, Felicia; Park, Lawrence P; Sharma-Kuinkel, Batu K; Souli, Maria; Morse, Alison M; Eichenberger, Emily M; Hale, Lauren; Kohler, Celia; Warren, Bobby; Hansen, Brenda; et al.
Abstract: Background: To understand the clinical, bacterial, and host characteristics associated with recurrent Staphylococcus aureus bacteremia (R-SAB), patients with R-SAB were compared to contemporaneous patients with a single episode of SAB (S-SAB). Methods: All SAB isolates underwent spa genotyping. All isolates from R-SAB patients underwent pulsed-field gel electrophoresis (PFGE). PFGE-indistinguishable pairs from 40 patients underwent whole genome sequencing (WGS). Acute phase plasma from R-SAB and S-SAB patients was matched 1:1 for age, race, sex, and bacterial genotype, and underwent cytokine quantification using 25-analyte multiplex bead array. Results: R-SAB occurred in 69 (9.1%) of the 756 study patients. Of the 69 patients, 30 experienced relapse (43.5%) and 39 reinfection (56.5%). Age, race, hemodialysis dependence, presence of foreign body, methicillin-resistant Staphyloccus aureus, and persistent bacteremia were individually associated with likelihood of recurrence. Multivariate risk modeling revealed that black hemodialysis patients were nearly 2 times more likely (odds ratio [OR] = 9.652 [95% confidence interval [CI], 5.402–17.418]) than white hemodialysis patients (OR = 4.53 [95% CI, 1.696–10.879]) to experience R-SAB. WGS confirmed PFGE interpretations in all cases. Median RANTES (regulated on activation, normal T cell expressed and secreted) levels in acute phase plasma from the initial episode of SAB were higher in R-SAB than in matched S-SAB controls ( P  = .0053, false discovery rate < 0.10). Conclusion: This study identified several risk factors for R-SAB. The largest risk for R-SAB is among black hemodialysis patients. Higher RANTES levels in R-SAB compared to matched controls warrants further study. Abstract : This study identified several risk factors for recurrent Staphylococcus aureus bacteremia (R-SAB). The largest risk for R-SAB is among black hemodialysis patients. Higher RANTES levels in R-SAB compared to matched controls warrants further study.